Home births in England and Wales, 1979: perinatal mortality according to intended place of delivery. Issue 6447 (22nd September 1984) - Campbell, R; Davies, I M; Macfarlane, A; Beral, V
Abstract : A survey was carried out of all 8856 births occurring at home in England and Wales in 1979. Of these births, 67% had been booked for delivery at home, 21% had been booked for delivery in hospital, 3% had not been booked, and for 9% the intended place of delivery was unknown. The perinatal mortality varied almost 50-fold according to the intended place of delivery, ranging from 4.1/1000 births in those booked for delivery at home to 196.6/1000 unbooked births. Deliveries that occurred at home but had been booked for a hospital consultant unit were associated with a perinatal mortality of 67.5/1000. Births that had been booked for delivery at home included the smallest proportion of babies of low birth weight: 2.5% weighed 2500 g or less compared with 18% of those booked for consultant units and 29% of those not booked. Within these low birthweight groups there were noticeable differences in perinatal mortality; births booked to occur at home had the lowest mortality and unbooked births had the highest. Perinatal mortality among babies who weighed more than 2500 g was generally low irrespective of the intended place of delivery; the only exception was in babies whose delivery had not been booked. In all groups perinatal mortality was considerably higher in nulliparous than parous women. Women booking a delivery at home are clearly a selected group, and some may have been transferred to hospital during labour and were thus not included in the survey. Nevertheless, these data suggest that the perinatal mortality among births booked to occur at home is low, especially for parous women.